Severe necrotizing enteritis in a Sumatran rhinoceros (Dicerorhinus sumatrensis) - Zainuddin, Zainal Zahari; Abdul Rahman, Sheikh Omar; Abdullah, Mohd Tajuddin (1989)
A severe necrotising enteritis in a captive Sumatran rhinoceros is described. The lesions were highly suggestive of a Salmonella infection. Attempts to isolate the bacteria were however unsuccessful.